2011
DOI: 10.1074/jbc.m111.271684
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase (PI3K(p110α)) Directly Regulates Key Components of the Z-disc and Cardiac Structure

Abstract: Maintenance of cardiac structure and Z-disc signaling are key factors responsible for protecting the heart in a setting of stress, but how these processes are regulated is not well defined. We recently demonstrated that PI3K(p110␣) protects the heart against myocardial infarction. The aim of this study was to determine whether PI3K(p110␣) directly regulates components of the Z-disc and cardiac structure. To address this question, a unique three-dimensional virtual muscle model was applied to gene expression da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…We recently reported that genes encoding key components of the Z-disc are also depressed in hearts of dnPI3K mice [38]. This suggests that the dnPI3K heart can compensate for these abnormalities under normal conditions but not under conditions of stress such as diabetes, resulting in accelerated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that genes encoding key components of the Z-disc are also depressed in hearts of dnPI3K mice [38]. This suggests that the dnPI3K heart can compensate for these abnormalities under normal conditions but not under conditions of stress such as diabetes, resulting in accelerated cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In murine cardio myocytes, constitutive activation and dominant-negative expression of PI3Ka leads to reciprocal regulations in the gene expression of Z-disk and costamere proteins. Accordingly, PI3Ka activity affects in vivo the number and thickness of myofilaments and myofibrils in cardiomyocytes [82]. In the same study, PI3K inhibitors PIK75 and A66 were reported to modify in vitro cardiomyocyte morphology and to reduce IGF-1-induced myofiber maturation.…”
Section: Pi3kamentioning
confidence: 96%
“…This is an extremely minimalistic view of the Z-disc, since the plethora of proteins that localises to that part of the sarcomere has been left out for reasons of simplification. For recent excellent reviews on the Zdisc, see Faulkner et al (2001) and Frank et al (2006); for a recent 3D model of the Z-disc, see Waardenberg et al (2011) the sarcomeres are established (Fritz-Six et al 2003;Chu et al 2003;Ehler et al 2004), leiomodin expression can only be detected at later stages of heart development in the embryo (Tsukada et al 2010). In cultured cardiomyocytes, the presence of leiomodin seems to be a marker of sarcomere maturity (Skwarek-Maruszewska et al 2010).…”
Section: How Is Thin Filament Length Regulated?mentioning
confidence: 96%